Tree health assessment and maintenance practices in Taman Tasik Titiwangsa, Kuala Lumpur - Badrulhisham, Norainiratna (2013)
Trees are very important element in the construction of garden and landscape area. The health status of trees in urban park has not been fully studied and less maintenance attention given compared to roadside trees. Trees that are not properly maintained are susceptible to stress and various factors that may cause poor health. This research conducted in Titiwangsa recreational park among 654 sampled trees to determine and evaluate health of trees by visual assessing the trunk, crown, leaves and branches condition by using modified ‗Tree health form‘ by Sajan (2000). Health status of each trees was then evaluate based on tree health adapted from the rating systems established by the ‗Council of Tree and Landscape Appraisers‘ by International Society of Arboriculture (ISA), (2000). Besides that, interviews were conducted among tree maintenance officer and workers to determine their actual maintenance practices including technique, frequency, personnel, equipment and material used in tree maintenance. Feedbacks from respondents helps in determine the possible factors that implicate the poor health of the trees. Results found that the health status of trees in Titiwangsa recreational park were in fair (63.1%) to good (30.4%) health status. Only less than 6.6% with poor (6.3%) and dead tree (0.2%) indicates that most of the trees in the study area suffered from many structural and mechanical damages, poor crown health and have poor vigor. Majority of trees with big and medium size were fair health status with 74% and 61% while majority of small size trees with good health status (54%) from the frequency distribution. Tree health problems that showed high incidence and severity are cankers or galls on trunk, dead and broken of branches, other plants growing on trunk and unbalanced crown density. From the research, it was also found that maintenance practices done are still inadequate and is less than satisfactory. Most of the problems of tree health were caused by improper pruning techniques and lack of disease and pest control. Action should be taken to prevent the occurrence of poor health of trees in the future that could pose a danger to park visitors.